Pacental Tuberculosis About One Case and Literature Review About One Case and Literature Review: Placental Tuberculosis - Andrianarison, Lofo Heriniaina; Ranaivomanana, Volahasina Francine; R. H. N., Rabarijaona; Randrianjafisamindrakotroka, Nantenaina Soa (International Journal For Research In Biology & Pharmacy, 2022)
Tuberculosis is an endemic disease in poor country comprising Madagascar. There are no many report about tuberculosis associated with pregnancy and placental examination is rarely reported. The insidious manifestation of tuberculosis in pregnant woman and the apparition of the signs few days post partum in the newborn cause the late of diagnosis. By the mechanism, the site and means of dissemination, the placental tuberculosis is divided in five histological categories: decidual, intervillous, intravillous, amniotic and chorioamniotic intravascular. Fetal transmission is suspected in intrachorial tuberculosis. Fetal transmission is rare if the mother is treated normally but can be favored by HIV coinfection. We report a case of 31 years old woman in 38 weeks of amenorrhea with antecedent of pleural tuberculosis under treatment during 2 months. Placental histological examination showed decidual tuberculosis. Our aims are to describe histological feature of placental tuberculosis and to compare it with the literature.